The Influence Of Leadership Style, Organizational Culture, And Job Satisfaction On Employee Loyalty Of PT. Anugerah Mahadaya Nusantara Banjarmasin - Rina, Rina; Syamsuddinnor; Nurhikmah (International Journal of Economics, Business and Innovation Research, 2025)
This research aims to: First, analyze the partial effect of leadership style on employee loyalty at PT. Anugerah Mahadaya Nusantara Banjarmasin. Second, analyze the partial effect of organizational culture on employee loyalty at PT. Anugerah Mahadaya Nusantara Banjarmasin. Third, analyze the partial effect of job satisfaction on employee loyalty at PT. Anugerah Mahadaya Nusantara Banjarmasin. Fourth, analyze the simultaneous effect of leadership style, organizational culture, and job satisfaction on employee loyalty at PT. Anugerah Mahadaya Nusantara Banjarmasin.The population in this study consists of all permanent employees of PT. Anugerah Mahadaya Nusantara Banjarmasin, and the sample is the entire population, totaling 40 respondents. This study is a quantitative research using a descriptive quantitative approach. The analysis tools used in this study include validity and reliability tests for the data. The hypothesis testing methods used are the F-test and t-test.Based on the results of the research conducted, the following conclusions can be drawn: First, leadership style has a partial effect on employee loyalty at PT. Anugerah Mahadaya Nusantara Banjarmasin. Second, organizational culture has a partial effect on employee loyalty at PT. Anugerah Mahadaya Nusantara Banjarmasin. Third, job satisfaction has a partial effect on employee loyalty at PT. Anugerah Mahadaya Nusantara Banjarmasin. Fourth, leadership style, organizational culture, and job satisfaction have a simultaneous effect on employee loyalty at PT. Anugerah Mahadaya Nusantara Banjarmasin.For future research, it is recommended to further develop the factors that influence employee loyalty in the future. In addition, upcoming studies could use a broader subject of research with a larger sample size. Future research is also expected to add more items to the questionnaire to provide a more detailed measurement of each indicator, include independent variables that were not studied in this research, and incorporate other dependent variables such as employee performance.